Housing, consumption and monetary policy: How different are the US and the euro area? - Musso, Alberto; Neri, Stefano; Stracca, Livio (Journal of Banking & Finance, 2011)
This paper provides a systematic empirical analysis of the role of the housing market in the macroeconomy in the US and the euro area. First, it establishes some stylised facts concerning key variables in the housing market on the two sides of the Atlantic, such as real house prices, residential investment and mortgage debt. It then presents evidence from Structural Vector Autoregressions (SVAR) by focusing on the effects of monetary policy, credit supply and housing demand shocks on the housing market and the broader economy. The analysis shows that similarities outweigh differences as far as the housing market is concerned. The empirical evidence suggests a stronger role for housing in the transmission of monetary policy shocks in the US. The evidence is less clear-cut for housing demand shocks. Finally, credit supply shocks seem to matter more in the euro area.